Peningkatan Keterampilan Menulis Naskah Drama Dengan Media Cerpen Oleh Peserta Didik Di Kelas XI SMK Negeri 7 Medan - Mey Waty Silaban; Nadra Amalia; Lukmi Sibarani (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
Based on the results of interviews with Indonesian language subject teachers at SMKN 7 Medan, the obstacles encountered in learning to write drama scripts were regarding the methods and learning media used were ineffective, resulting in low scores for students who were under the KKM. Therefore, to overcome this, researchers use short story media in writing drama scripts. The research objective is to improve the learning outcomes of writing drama scripts for class XI MPLB students at SMKN 7 Medan. The method used is Class Research method. This is because this class research collaborative method aims not to test a treatment but a way to make changes towards improvement or improvement in learning. There are 2 cycles in this study, there are 2 instruments, namely tests. The test instrument was in the form of drama script results in both cycles. The first cycle reached an average of 76.80 while the second cycle average increased to 86.80. By looking at the average value, students have achieved a score above the KKM that has been determined, namely 75. After learning to write drama scripts with short story media, students become more active and find it easier to think creatively to put their ideas into the script. drama and motivation to learn in students increases.